Cohesion in Moghanehee Distiches of Khaghni and Hafez Based on Halliday’s Systemic Functional Theory - Tahereh Babakhani; Ali Heidary; Masud Sepahvandi (مطالعات زبانی و بلاغی)
The analysis of literary texts owes a great deal to Halliday and Hassan’s Systemic Functional Theory. In this theory, language is the primary tool to convey culture. Each aspect of culture is introduced through specific function in holistic system. This text based approach possesses various tools in order to demonstrate cohesion in the text to transfer the connotation in speaker/writer’s mind which is considered as independent variable in this study, whereas the impact of Khaghani on Hafez in literal and meaning to create inner and outer structure of Moghanehee (a type of love poetry) has been chosen as dependent variable. Khaghani (1140-1215) was one of the most important poets had written Moghanehee poetry after Sanaee( 1094-1166) and Attar(1121-1239) and prior to Mawlavi (1270- 1339) and Hafez(1348-1413). Among the previous poets, Hafez was strongly influenced by Khaghni. Based on Halliday’s Systemic Functional Theory, this study tries to reveal the cohesion amount and its creating factors in the distiches of poems. From the distribution frequency and their percentages, it was concluded that the presence amount of cohesion tools in Kaghani’s Moghanehee distiches were more than Hafez’s. The statistical society in this study is 60 distiches (beit) from Moghanehee distiches of Khagani and Hafez. 30 distiches were chosen from each poet.